2022
DOI: 10.3390/antiox11020199
|View full text |Cite
|
Sign up to set email alerts
|

SBT (Composed of Panax ginseng and Aconitum carmichaeli) and Stigmasterol Enhances Nitric Oxide Production and Exerts Curative Properties as a Potential Anti-Oxidant and Immunity-Enhancing Agent

Abstract: Immune dysregulation is a risk factor for several diseases, including infectious diseases. Immunostimulatory agents have been used for the treatment of immune dysregulation, but deleterious adverse effects have been reported. The present study aims to establish the anti-oxidant and immunity-enhancing effects of Sambu-Tang (SBT), composed of Panax ginseng and Aconitum carmichaeli, and stigmasterol (Stig), an active compound of SBT. Immune-related factors were analyzed in RAW264.7 macrophage cells, mouse primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Macrophages play an important role in the regulation of immune response and this function depends on the secretion of pro-inflammatory cytokines such as IL-6 and TNF-α [ 42 , 43 ]. Previous studies reported that various plant extracts enhanced secretions of the cytokines [ 44 , 45 ]. Thus, AHL and AHR extracts significantly enhanced the productions of IL-6 and TNF-α and can affect immune system by controlling the secretion of pro-inflammatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages play an important role in the regulation of immune response and this function depends on the secretion of pro-inflammatory cytokines such as IL-6 and TNF-α [ 42 , 43 ]. Previous studies reported that various plant extracts enhanced secretions of the cytokines [ 44 , 45 ]. Thus, AHL and AHR extracts significantly enhanced the productions of IL-6 and TNF-α and can affect immune system by controlling the secretion of pro-inflammatory cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Tese compounds increase NO production by macrophage cell lines. Low doses, 1-10 μM, of hexadecanoic acid, octadecanoic acid, Stigmasterol-treated RAW264.7 cells produced elevated levels of NO compared to the control [63]. Tis study revealed the capacity of T. brownii stems bark DCM extract to elevate TNF-α levels in macrophages isolated from pyrogallol-immunosuppressed mice.…”
Section: Discussionmentioning
confidence: 86%
“…Low doses, 1–10 μ M, of hexadecanoic acid, octadecanoic acid, and linoleic acid enhanced NO production by J774 cells [ 62 ]. Stigmasterol-treated RAW264.7 cells produced elevated levels of NO compared to the control [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence was carried out as described previously ( Han et al, 2022a ). The antibody specific for PD-L1 was used at a 1:500 dilution, and anti-mouse IgG H&L (Alexa Fluor ® 647) was used at a 1:1,000 dilution.…”
Section: Methodsmentioning
confidence: 99%